Supply Chain Risk Management for Macro Risks - Munson, Chuck (Charles Lee); Klumpp, Matthias; Abidi, Hella (Pearson, 2013)
This new case study focuses on the macro risks associated with relying on global supply chains. It addresses large events including floods, earthquakes, hurricanes, fires, and tornadoes; manmade disasters such as wars and economic crises; and technical disasters ranging from transport accidents and explosions to fires, gas leaks, and industrial accidents. Coverage includes risk classification; strategic, tactical, and operational issues; and a complete supply chain resilience model designed to help both students and practitioners effectively integrate macro risks into planning. Authors: Matthias Klumpp and Hella Abidi; both from FOM University of Applied Sciences.